1996
DOI: 10.1091/mbc.7.7.1075
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 4 in 3T3-L1 adipocytes: regulation by insulin and participation in insulin-dependent glucose transport.

Abstract: Syntaxins are thought to be membrane receptors that bind proteins of the synaptobrevin/ vesicle-associated membrane protein (VAMP) family found on transport vesicles. Recently, we detected synaptobrevin II and cellubrevin on immunopurified vesicles containing the glucose transporter 4 (GLUT4) in insulin-responsive cells. In an effort to identify the plasma membrane receptors for these vesicles, we now examine the expression of syntaxins in the 3T3-L1 adipocyte cell line. Neither syntaxin 1A nor 1B was found, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
111
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 38 publications
11
111
0
Order By: Relevance
“…The fidelity of this process is mediated at least in part by SNARE proteins [27]. In adipocytes and muscle, the SNAREs syntaxin 4 and VAMP2 have been identified as being of crucial importance in insulin-stimulated GLUT4 translocation [7,12,28,29]. We have previously demonstrated that expression of syntaxin 4 and VAMP2 is increased in muscles derived from SHRSP animals compared with in WKY animals [6], in addition to in the Zucker diabetic fatty rat [30].…”
Section: Discussionmentioning
confidence: 98%
“…The fidelity of this process is mediated at least in part by SNARE proteins [27]. In adipocytes and muscle, the SNAREs syntaxin 4 and VAMP2 have been identified as being of crucial importance in insulin-stimulated GLUT4 translocation [7,12,28,29]. We have previously demonstrated that expression of syntaxin 4 and VAMP2 is increased in muscles derived from SHRSP animals compared with in WKY animals [6], in addition to in the Zucker diabetic fatty rat [30].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the presence of syntaxins 3 and 4 on either the apical or basolateral surface, respectively, strongly suggests that they are involved in polarized vesicular transport pathways to these surfaces. It is interesting that syntaxin 3 is not expressed in adipocytes (Volchuk et al, 1996), which do not possess an apical surface, or in hepatocytes (Figure 1; Bennett et al, 1993), which have an apical plasma membrane but lack a direct pathway from the TGN to this surface (Hubbard, 1991). Together, this might suggest that syntaxin 3 functions at the apical surface of polarized cells and could be potentially involved in the biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this work has generally examined the role of a single v-SNARE/t-SNARE combination. To our knowledge, only two reports have examined the role of multiple syntaxin isoforms in a single, nonpolarized cell type, i.e., in adipocytes (Volchuk et al, 1996) and macrophages (Hackam et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Specific SNARE isoforms are expressed in muscle and fat cells, i.e., VAMP2 and VAMP3/cellubrevin (hereafter called VAMP3) (Cain et al, 1992;Volchuk et al, 1994Volchuk et al, , 1995, syntaxin4 Volchuk et al, 1996), and SNAP-23 (SNAP-25-like protein of 23 kDa) (Wang et al, 1997;Wong et al, 1997;Rea et al, 1998). The participation of the target membrane (t)-SNAREs syntaxin4 (Cheatham et al, 1996;Olson et al, 1997) and SNAP-23 (Rea et al, 1998;Foran et al, 1999;Foster et al, 1999b) in GLUT4 translocation has been implicated with the use of various molecular and biochemical approaches, such as the introduction of botulinum toxins and neutralizing antibodies into 3T3-L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%